Government-linked investment companies' shareholdings and tax aggressiveness / Rahayu Abdul Rahman... [et al.] - Abdul Rahman, Rahayu; Mahmud, Nur Farizan Mazhani; Zaini, Naimah; Meor Zawawi, Maizura (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM), 2018)
The purpose of this study is to investigate the impact of government institutional shareholdings via government-linked investment companies (GLICs) on tax aggressiveness strategies of Malaysian government-linked companies (GLCs). This study uses effective taxes rate (ETR) and tax paid to operating cash flow (TPOC) as proxies of tax aggressiveness. The GLCs will be classified as tax aggressive firms if the ETR and TPOC are less than the corporate statutory tax rates. Using a sample of 75 firm-year observations of Malaysian GLCs listed on Bursa Malaysia from 2010 to 2014, this study finds that GLCs are less likely to engage in tax aggressive. The findings show that there is a significant and negative relationship between GLICs shareholdings and tax aggressiveness. The evidence suggests that GLICs are the effective government institutional investors in mitigating tax aggressive strategies of their portfolio firms. In addition, this study provide empirical evidence to highlight the commitment of GLICs in protecting government revenues by avoiding aggressive tax planning in their portfolio firms in order to assist government's social and political objectives. This study is one of the few studies that examine the effectiveness of GLICs monitoring in mitigating tax aggresiveness in GLCs. This study extend prior studies by using both conforming and non confirming measures of corporate tax avoidance andsegregating GLICs shareholding into two categories; Federal Government Pension Investment Funds (FGPIF) and other GLICs (OFGLIC).